Strengthening of RC beam-column joints using steel plate with shear connectors: Experimental investigation. (January 2022) - Ebanesar, Arunraj; Gladston, Hemalatha; Noroozinejad Farsangi, Ehsan; Sharma, Samurailatpam Vivekananda
Highlights: Provision of steel plate with shear connectors in the beam-column joints. Reduce the congestion of shear reinforcement and increase shear strength in the panel zone. Provision of steel plate with shear connectors to avoid joint shear failure. Improving the seismic resilience of RC structures in seismic prone areas. Abstract: This paper presents experimental analyses on beam-column joints strengthened with steel plate & steel plate with shear connectors subassemblies subjected to cyclic loading. For the investigation, a total of six reduced-scale external beam-column joints were cast. Two specimens with individual closed stirrups are used as the reference models. Among the remaining, two specimens were strengthened with steel plates and two specimens were retrofitted with steel plates and shear connectors. The reinforced beam-column subassemblies were subjected to cyclic tests to determine their crack propagation and resistance capability during seismic excitations. The primary objectives of the analyses have been to monitor the seismic performance of the joints in terms of load–displacement pattern, hysteresis behavior, failure pattern, and energy dissipation capability. In addition, some experiments were carried out to differentiate and evaluate the efficiency of conventionally closed stirrups. The results are inspiring as the steel plate with shear connectors outperformed the traditional stirrups in terms of lateral strength, stiffness, and accumulated energy dissipation. The results indicated that the proposed methodology can be used as a feasible and adequate technique to improve the seismic resilience of RC structures in regions of high seismicity.